Mother's Perception of the Effect of the Bina Keluarga Balita (BKB) Program on Growth Development - Raihan Raihan; Iskandar Iskandar; Alfriedsyah Alfriedsyah; Agus Hendra Al Rahmad (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
The Bina Keluarga Balita (Toddler Family Development) program is designed to monitor and handle problems in the community. Mother's perception of this program should be assessed to find out their understanding of this program, monitor the growth of toddlers by examining the Kartu Menuju Sehat (Health Care Cards), and observe the development of toddlers by examining the Kartu Kembang Anak (Child Development Cards). This study aims to assess mothers' perception of the influence of the Bina Keluarga Balita program on the growth and development of toddlers. This quantitative research employed a cross-sectional design. The data were processed using a chi-square test. This study involved 45 mothers of children under five, The sampling was determined using the Lameshow formula. This study has revealed a relationship between mothers' perception of the growth and development of toddlers, as shown by the statistical result of p < 0.05. Meanwhile, the relationship between the mothers' perception of the growth and development of toddlers has a p-value = 0.007. Finally, the relationship between the mother's perception of the development and the development of toddlers has a p-value = 0.017. It is concluded that the mothers’ perception and toddlers' growth and development have an interrelated relationship. Thus, a good perception will create more significant growth and development in toddlers.